Scientific Opinion of Flavouring Group Evaluation 500 (FGE.500): rum ether. (24th August 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; et al.
Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to deliver a scientific opinion on the implications for human health of the flavouring rum ether [FL‐no: 21.001] in the Flavouring Group Evaluation 500 (FGE.500), according to Regulation (EC) No 1331/2008 and Regulation (EC) No 1334/2008 of the European Parliament and of the Council. Rum ether is a complex mixture of volatile substances obtained by distillation of the reaction products of pyroligneous acid and ethyl alcohol under oxidative conditions in the presence of manganese dioxide and sulfuric acid. A total of 84 volatile constituents have been reported by the applicant. It is a colourless liquid with a rum‐like odour and flavour. Its major uses are in the food categories beverages, confectionery and baked goods. The Panel decided to apply a congeneric group‐based approach. The 84 reported constituents were allocated to 12 congeneric groups, based on structural and metabolic similarity. For eight of the congeneric groups, the Panel concluded that there is no safety concern at the intended conditions of use. However, the Panel concluded that substances in congeneric group 1 (ethanol and acetaldehyde) and congeneric group 12 (furan) are carcinogenic and genotoxic. The Panel also identified genotoxicity concerns for substances in congeneric group 3 (3‐pentene‐2‐one). The exposure for congeneric group 10 (ethers of various structures) was above the Threshold of Toxicological Concern (TTC) applicable for this group, but a point of departure or health based guidance value that covers all the substances in this group could not be identified. The Panel concluded that according to the overall strategy for the risk assessment of flavouring substances, the presence of genotoxic substances as process‐derived constituents of rum ether is of safety concern.